The Impact of Neutrophil-to-Lymphocyte and Platelet-to-Lymphocyte Ratios in Epithelial Ovarian Cancer - Samet Kirat; Utku Akgor (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: This study aims to investigate the prognostic value of the preoperative neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients with epithelial ovarian cancer.